Late Onset Segmental Neurofibromatosis (Mosaic Neurofibromatosis Type 1): A Case Report with Review of Literature - Rana, Arnija; Joshi, S; Pudasaini, S (Nepal Medical College Journal, 2019)
Segmental neurofibromatosis (SNF) is a rare manifestation of neurofibromatosis. Very few cases have been reported in older population. Here, we present a case of 73 year old male with four years history of multiple, skin coloured, dome shaped, soft nodules situated over left lumbar region. The histopathological evaluation of the excised nodule revealed neurofibroma. Recognition of this condition is important, as there may be associated systemic involvement, malignancies and possibility of transmission to the offspring.